Primer reporte de Tanaostigmodes sp. como plaga principal de Caesalpinia spinosa: Aspectos morfológicos y biológicos. - Murga-Orrillo, H. (2021)
The tara (Caesalpinia spinosa (Mol.) Kuntze) is a non-timber forest species whose pods are of economic importance to various industries; however, attacks by pests such as Tanaostigmodes sp. the leaves and young stems decrease the production of this species. The aim of this study was to determine the morphological and biological characteristics of Tanaostigmodes sp. and percentage of incidence in C. spinosa. 1399 insects were identified in which evaluations of the duration of the stages, the morphometry and the damage to the plant were carried out. The egg, larva, pupa and adult measure 0.2, 2.0, 2.1 and 2.0 to 2.3 mm long, last 13.1, 71.8, 20.6 and 10.1 days respectively, totaling its development cycle in 115.1 days; the larvae when feeding make mines in the rachis of the leaves and in young stems, reaching maximum attacks of up to 84.5% causing defoliation. Tanaostigmodes sp. it is a major tare pest, with average attack records of 24.6% on leaves. Knowing its biological aspects and its interaction with tara phenology will allow the adoption of efficient strategies for its integrated management and control.